Cultural capital, the digital divide, and the health of older adults: a moderated mediation effect test - Yupeng Cui; Youshi He; Xinglong Xu; Lulin Zhou; Jonathan Aseye Nutakor; Lingqing Zhao (BMC, 2024)
Abstract Background It is of great practical significance to study the intrinsic relationship between cultural capital, digital divide, cognitive ability, and health of older adults in the dual social context of population aging and the digital era. Methods We analyzed data from the 2020 China Family Panel Studies (CFPS) initiated by the China Center for Social Science Surveys at Peking University. Physical health, mental health, and memory health were set as indicators of older adults, and the relationship between cultural capital, digital divide, cognitive ability, and health of older adults was examined by hierarchical regression with moderated mediated effect methods. Results Improvement in the health of older adults is associated with an increase in the level of cultural capital; cultural capital may bridge the digital divide faced by older adults, which in turn promotes the improvement of the health of older adults; the higher the level of cognitive ability, the stronger the effect of cultural capital on the digital divide, and at the same time, the stronger the mediating effect of the digital divide; cultural capital has a more pronounced effect on the health of older male adults living in the city. Conclusions The results of the study show that cultural capital can have a positive impact on the health of older adults, but there is urban-rural heterogeneity and gender heterogeneity, in which the digital divide plays a mediating role, and the enhancement of the cognitive ability of older adults will be conducive to the improvement of their health, so the health of older adults should be promoted by improving the level of their cultural capital and the ability of older adults to use digital technology, thus provide references for the protection of health of older adults.